Improving English Listening Skills Through Audio-Visual For Students - Kori Pamangin (International Journal of Management and Education in Human Development, 2022)
Writing this classroom action research aims to determine whether the Audio-Visual learning model can improve student activity and achievement. The data collection methods are observation and learning achievement tests. The data analysis method is descriptive both for qualitative data and quantitative data. The results obtained from this study are Audio-Visual can increase student activity and achievement. This is evident from the results obtained in Cycle I is 6.3 for learning achievement. From Cycle I to Cycle II rose to 7.9 for learning achievement. The conclusion obtained from this study is that the Audio-Visual learning model can improve learning achievement